Pesantrenpreneur: Strategi Entrepreneurship di Pondok Pesantren Melalui Komoditas Talas Satoimo - Arinal Rahmati; Husnurrosyidah Husnurrosyidah; Muhammad Dian Ruhamak (Equilibrium: Jurnal Ekonomi Syariah, 2020)
This study aims to determine the strategy of the pesantrenpreneur in Islamic boarding school Ummul Ayman Pidie Jaya Aceh in producing students to have a good entrepreneurial spirit. This research uses a descriptive qualitative approach. This study's data were collected through in-depth interviews with informants and then matched the research results through interviews with documentary evidence that the authors had collected and processed it with the stages of data reduction, data presentation, and conclusion drawing. The results showed that it is necessary to develop an entrepreneurial interest in students to explore their potential, where apart from prayer is also accompanied by effort. With the increasing interest in entrepreneurship and getting to know market segmentation and also how to deal with consumers who have various behaviors, their creativity will emerge, which will have an impact on increasing the economic value of raw material products which may be developed in the form of semi-finished or even processed products. Ready for consumption, considering the high demand for this commodity will directly result in an increased trade surplus and a relatively good economic outlook. Besides, students also have businesses and become entrepreneurs so that they can become financially independent. Support from the local, regional government is also needed to run well and sustainably, which will impact the regional economy.